Efficient degradation of ciprofloxacin by Co3O4/Si nanoarrays heterojunction activated peroxymonosulfate under simulated sunlight: Performance and mechanism. Issue 3 (June 2022) - Yao, Li; He, Xinmeng; Lv, Jun; Xu, Guangqing; Bao, Zhiyong; Cui, Jiewu; Yu, Dongbo; Wu, Yucheng
Abstract: The development of stable and efficient photocatalysts to activate peroxo monosulfate (PMS) is of great significance in water treatment, but it is still a major challenge. In this paper, Co3 O4 /Si nanoarrays (Co3 O4 /SiNWs) heterojunction is successfully synthesized through simple and effective approaches, and the peroxymonosulfate (PMS) assisted photocatalytic degradation system based on the Co3 O4 /SiNWs heterojunction under simulated sunlight is constructed for ciprofloxacin (CIP) degradation. The Co3 O4 /SiNWs-30/PMS system exhibits a high CIP photocatalytic degradation rate of 93.51% and a kinetic constant of 0.0474 min −1 in 60 min accompanied with good degradation stability. The appropriate energy band structure of Co3 O4 /SiNWs heterojunction allow the formation of internal electric field, resulting in the establishment of a typical Z-scheme charge transfer system. On the one hand, the formed Co3 O4 /SiNWs Z-scheme heterojunction can synchronously inhibit the recombination of photo-generated electron-hole (e - -h + ), which promotes the transfer of photogenerated carriers and improve the photocatalytic activity. On the other hand, photogenerated e - contribute to produce active radicals by activating PMS, and photogenerated h + can also be directly used as active radicals, thereby realizing high-efficiency photocatalytic degradation. This work gives a good insight into the photocatalytic degradation of antibiotics in water. Graphical Abstract: ga1 Highlights: Co3 O4 /SiNWs/PMS system was successfully prepared for CIP degradation. A degradation rate of 93.51% and a kinetic constant as high as 0.0474 min-1 were obtained under simulated sunlight. The Co3 O4 /SiNWs had the advantages of simple recovery operation, strong reusability and low Co leaching amount. Mechanism of charge transfer and photocatalysis based on Co3O4/SiNWs was well studied.